Geoelectrical survey for evaluation of groundwater potential within the basaltic terrain of Chikotra river basin, Maharashtra (India) - Tahama, Khan; Gupta, Gautam; Patil, J.D. (My University, 2021)
Geoelectrical data was acquired using Wenner array over 23 sites with constant electrode separation of 70 m over Chikotra Basin, Dist. Kolhapur, Maharashtra (India). The spatial variation maps of resistivity at depths from 2 to 70 m were plotted using Inverse Distance Weighted (IDW) technique for interpolation in ArcGIS 10.5 to obtain a comprehensive subsurface hydrogeological representation of the study area. High resistivity (>140 Ωm) up to 20m depth, indicative of massive basalts is deciphered towards the NE part of the study area, while the NW sector reveal low resistive (up to 40 Ωm) feature at shallow depths due to fractured basalts, thus conducive for groundwater exploration. Alluvium deposits and columnar jointed basalts in the central part depicts as EW trending conductive (< 30 Ωm) feature suggesting prospective groundwater zone. Low resistivity (6-50 Ωm) from shallow to deeper depths (up to 70m), in the southern region can be identified as potential aquifer system. Longitudinal geoelectric cross-sections are generated over four profiles to identify the lateral and vertical variation in geology and groundwater potential zones. The western and central part of the northern profile (A-A') is highly resistive with resistivity of the order of 80- 140 Ωm constituting compact basalts and thus devoid of water. Low resistive zone (30 Ωm) in the eastern part suggests groundwater at shallow depths. Low resistivity zones ranging from 10-50 Ωm is observed at different depth levels over the central profile (BB') which can be tapped for groundwater exploitation. Several sites over profiles C-C' and the southern-most D-D' suggest promising aquifer zones. Because defining prospective groundwater zones in hard rock terrain is difficult, it’s crucial to look into a river basin’s hydrogeological arrangement early on in the planning process
Keywords: Chikotra River; Groundwater; Inverse Distance Weighted; Maharashtra; Resistivity